Association of elevated resting pulse rate with increased risk of hypertension development in children: A prospective study in Suzhou, China. Issue 32 (August 2017) - Hu, Jia; Shen, Hui; Chu, Guang-Ping; Fu, Han; Huang, Fei-Fei; Zheng, Yan-Min; Han, Di; Zhou, Yi-Kai; Wang, Qi; Wang, Bo; Teng, Chen-Gang; Liu, Fang; et al.
Abstract: Background: Elevated resting heart rate (RHR) or resting pulse rate (RPR) is associated with increased risk of hypertension development. However, information is limited to adults. The purpose of this study is to analyze this association among Chinese children in a prospective design. Methods: A total of 4861 children who participated in the Blood Pressure Surveillance Program (2011–2017) were selected in this research. To investigate the association between RPR and hypertension development, children were divided into 4 groups according to the quartiles of RPR at baseline. Odds ratios (ORs) with 95% confidence intervals (CIs) were calculated using logistic regression model. Results: Over a mean follow-up of 3.0 ± 0.1 years, there were 384 cases of incident hypertension. Compared to boys and girls in the 1st quartile, those in the 4th quartile were 1.73 (95% CI 1.13, 2.65), 2.22 (95% CI 1.43, 3.45) times more likely to have hypertension, respectively. Every 10 bpm increase in RPR was associated with a 26% greater risk of hypertension development in boys (OR: 1.26; 95% CI 1.10, 1.44), while this risk was 1.28 (95% CI 1.13, 1.44) in girls. Baseline blood pressure (BP) and body mass index (BMI) did not have significant interactions with RPR on risk of hypertension development. Conclusion: This study confirms the relationship between elevated RPR and increased risk of hypertension development in children, independent of confounders including baseline BP and BMI. An elevated RPR could be considered as a risk factor for the assessment of hypertension, no matter from a clinical setting or a public health perspective.